2016
DOI: 10.1136/thoraxjnl-2015-208023
|View full text |Cite
|
Sign up to set email alerts
|

Immature monocytes contribute to cardiopulmonary bypass-induced acute lung injury by generating inflammatory descendants

Abstract: The immature CD14CD16 monocytes might contribute to blood-circuit contact-induced acute lung injury by generating TNF-α-producing, mature monocytes. New strategies based on monocyte manipulation could be a promising therapeutic approach for minimising CPB-related lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
(40 reference statements)
2
21
0
Order By: Relevance
“…T-lymphocytes were shown to be activated during CPB and to induce pulmonary damage [ 32 ]. Our CPB group showed elevated plasma concentrations of cytokines of both Th1 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…T-lymphocytes were shown to be activated during CPB and to induce pulmonary damage [ 32 ]. Our CPB group showed elevated plasma concentrations of cytokines of both Th1 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…27 In the current study, we observed that prophylactic administration of methylprednisolone did not affect the percentage of immature Mo0 subsets which migrated into the peripheral blood from the bone marrow and spleen. 17 In addition, we found that methylprednisolone prophylaxis did not affect the percentage of inflammatory Mo2 subsets nor did it affect the expression levels of HLA-DR, CD86, CD64 and TLR-4 of each monocyte subset.…”
Section: Discussionmentioning
confidence: 62%
“…Next, we divided circulating monocytes into 4 subpopulations: CD14 low CD16 - (Mo0), CD14 high CD16 - (Mo1), CD14 high CD16 + (Mo2) and CD14 low CD16 + (Mo3) (Figure 2A). 17 The percentage of immature Mo0 monocytes rapidly increased during the CPB process, then returned to the normal range within 5 days post operation; following a slight decrease during CPB, inflammatory Mo2 monocyte subsets rapidly increased in the peripheral blood after CPB. Nevertheless, methylprednisolone did not significantly change the percentages (Figure 2B-E) and numbers of monocyte subsets (Figure 3A-D) in patients undergoing CPB.…”
Section: Resultsmentioning
confidence: 92%
“…The mechanism of CPB-induced lung injury has not been fully elucidated, which is affected by many factors. At present, CPB-induced lung injury is mainly related to CPB-induced systemic inflammatory response syndrome (SIRS), lung ischemia/reperfusion (IR) injury, and respiratory mechanical ventilation [ 1 , 2 ]. Pulmonary arterial perfusion (PAP) with hypothermic protective solution (HPS) is one of the measures to reduce lung IR injury.…”
Section: Introductionmentioning
confidence: 99%